Pemanfaatan Refugia dalam Meningkatkan Produksi Tanaman Padi Berbasis Kearifan Lokal - Icuk Muhammad Sakir; Desinta Desinta (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2018)
Sakir et al, 2018. Utilization of Refugia to Increase Rice Production Based on Local Wisdom. JLSO 7(1):97-105. The purpose of this study was to determine the utilization of refugia as a natural enemy of rice pest organisms in order to increase rice production sustainably. The study was conducted on a 3-hectare plot of land in Pemulutan Ulu Village, Pemulutan District, Ogan Ilir Regency, South Sumatra. The types of refugia that were used: sunflowers (Helianthus annuus), sesame (Sesamum indicum), zinnia flowers (Zinnia sp), yellow ray  flower (Cosmos caudatus) and marigold flower (Tagetes sp). The exploratory method was used with a cross sectional approach to analyze the intensity of the existence of natural enemies and rice pest disruptors, thus correlating with rice production. Observations were carried out for 18 weeks at 3 points with an area of 3 hectares. The rice varieties were used Ciherang (points A and C) and IR 42 (point B). The results showed an intensity of abundance of natural enemies or predators as many as 378 while the intensity of pests was 54 animals. The yield of rice was 8 tons/hectare,  8.3 tons/hectare and C is 8.1 tons/hectare for point A, B and C respectively. Utilization of refugia in rice plants was able to increase rice production by 15.1%.